Using Canva for Learning English: A Creative Approach - Nofiya Putri, Ilda Selli; Daviq Rizal (Universitas Islam Negeri (UIN) Mataram, 2024)
This article titled “Using Canva for Learning English: A Creative Approach” presents a quantitative research study that aimed to collect data on the perceptions of students towards the use of Canva as a media for English Language Teaching (ELT). The study was conducted among students of the English Language Education Study Program at UIN Walisomgo Semarang, and the research design was descriptive quantitative. The sample was selected using simple random sampling, and data was collected using a questionnaire with 15 questions as indicators. The procedures involved preparing instruments to collect data, using a questionnaire, and analyzing the data using descriptive quantitative research design. According to the findings of the study, students viewed Canva as a positive medium for ELT. This study sheds light on the efficacy of using Canva as a creative approach to English language learning.